Build customer loyalty through correlation management and experience with satisfaction mediation - Kadek Bagus Putra Permana; Ni Putu Nina Eka Lestari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study analyzed the influence of Customer Relationship Management (CRM) and Customer Experience on Loyalty, with Satisfaction as a mediating variable at PT. Fastrata Buana Denpasar. Based on the Social Exchange Theory, business correlations were built on mutually beneficial exchanges, where customers remained loyal if the perceived benefits exceeded the costs incurred. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used as a quantitative method to investigate the relationships between the variables. Business partners were given questionnaires to complete in order to gather data, including wholesalers, retailers, and kiosks. The outcomes indicated that CRM had a positive and significant impact on loyalty, both directly and through satisfaction as a mediator. Conversely, Customer Experience did not significantly influence loyalty, although it positively affected satisfaction. Furthermore, satisfaction partially mediated the correlation between CRM and loyalty but did not significantly mediate the correlation between Customer Experience and loyalty. These findings confirmed that CRM played a more dominant role in fostering loyalty than Customer Experience. PT. Fastrata Buana Denpasar was recommended to enhance personalized CRM strategies and strengthen communication to improve customer satisfaction and long-term loyalty.